A Clean Sharp Image: Don Cherry’s Suits as Sartorial Statements - Petrov, Julia (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
<em class="Italic" style="box-sizing: border-box; font-style: italic; caret-color: #161616; color: #161616; font-family: Karla, sans-serif; font-size: 16px; font-variant-caps: normal; font-weight: normal; letter-spacing: -0.4000000059604645px; orphans: auto; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">Canadian sports commentator Don Cherry is notorious for his outspoken opinions and flamboyant style, both attracting popular attention. This article examines his attention-grabbing on-air style as an extension of both his values for the game of hockey and his view of himself as a working-class boy made good. I argue that Cherry deliberately uses his suits to embody his social and personal values. Drawing on fashion studies approaches, I show that while not exactly fashionable in terms of trendiness, Cherry’s suits are examples of the ability of clothing to be indexical of working-class personality transformed.